Radio-loud Exoplanet-exomoon Survey: GMRT Search for Electron Cyclotron Maser Emission - Mayank Narang; Apurva V. Oza; Kaustubh Hakim; P. Manoj; Ravinder K. Banyal; Daniel P. Thorngren (The Astronomical Journal, 2022)
We conducted the first dedicated search for signatures of exoplanet–exomoon interactions using the Giant Metrewave Radio Telescope (GMRT) as part of the radio-loud exoplanet-exomoon survey. Due to stellar tidal heating, irradiation, and subsequent atmospheric escape, candidate “exo-Io” systems are expected to emit up to 10 ^6 times more plasma flux than the Jupiter-Io DC circuit. This can induce detectable radio emission from the exoplanet-exomoon system. We analyze three “exo-Io” candidate stars: WASP-49, HAT-P 12, and HD 189733. We perform 12 hr phase-curve observations of WASP-49b at 400 MHz during primary & secondary transit, as well as first & third quadratures achieving a 3 σ upper limit of 0.18 mJy beam ^−1 averaged over four days. HAT-P 12 was observed with GMRT at 150 and 325 MHz. We further analyzed the archival data of HD 189733 at 325 MHz. No emission was detected from the three systems. However, we place strong upper limits on radio flux density. Given that most exo-Io candidates orbit hot Saturns, we encourage more multiwavelength searches (in particular low frequencies) to span the lower range of exoplanet B-field strengths constrained here.